Collaborative Governance dalam Pengelolaan Kawasan Strategis Daerah Banten Lama - Amim Amrulloh; Ipah Ema Jumiati; Rina Yulianti (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2022)
Tourism has a high enough contribution to earn foreign exchange, and for this reason the government pays great attention to the tourism sector. Many efforts have been made by the government for the development of the tourism sector, one of which is the development of the Old Banten area as a strategic tourism area located in Serang City, Banten Province. The development of Banten Lama’s tourism encountered an obstacle in its management. There were several interests in the management, including the Banten Cultural Heritage Preservation Agency, the Serang City Government, and elements of the community so that the management of governance and collaboration between stakeholders can be carried out optimally. The purpose of this study is to identify the synergy between the government and the implementation of management of strategic tourism areas in Banten Lama. The Local Government is obligated to participate in implementing programs as such, in accordance with the mandate of the Law of the Republic of Indonesia. This research uses a case study approach with a descriptive method. The implementation of this activity carries Governance Collaboration by involving all parties in the development and tourism of the Regional Banten Lama Strategic Tourism Area.Keywords: collaborative government, development, tourism, Banten Lama